Studi Kasus Fonologis: Kesalahan Pengucapan Fonem Bahasa Indonesia pada Mahasiswa Asing di Universitas Muria Kudus - Suhaibatul Musdalifah (TALENTA, 2025)
This study discusses the mispronunciation of phonemes in Indonesian by foreignstudents from Timor Leste at Universitas Muria Kudus (UMK). The main purposeis to identify the forms of phonological errors as well as the factors causingphoneme pronunciation errors. This research used descriptive qualitativeapproach method, the data were collected through listening, recording, andinterview techniques. The results showed that errors mostly occurred in thechange of phonemes both consonants and vowels and the addition of consonantphonemes. These pronunciation errors are influenced by differences in thephonological system between the students' mother tongue and Indonesian.Although they do not cause changes in meaning, these errors have an impact onthe fluency of communication. Therefore, more intensive teaching of phoneticsand phonology is an important strategy to improve the language skills ofinternational students.